Group and semigroup rings : proceedings of the International Conference on Group and Semigroup Rings, University of the Witwatersrand, Johannesburg, South Africa, 7-13 July, 1985 - Karpilovsky, Gregory, 1940- (North-Holland mathematics studies ;, 1986)
A broad range of topics is covered here, including commutative monoid rings, the Jacobson radical of semigroup rings, blocks of modular group algebras, nilpotency index of the radical of group algebras, the isomorphism problem for group rings, inverse semigroup algebras and the Picard group of an abelian group ring. The survey lectures provide an up-to-date account of the current state of the subject and form a comprehensive introduction for intending researchers.